Analysis of Students' Perspectives of the Kurikulum Merdeka Implementation at SMP Swasta Kristen Tomosa 1 - Zai, Ayu Kartika; Telaumbanua, Kristof Martin Efori; Waruwu, Yaredi; Harefa, Afore Tahir (Journal Of Language Education and Development (JLed), 2025)
This study aims to analyze the perspectives of students at SMP Swasta Kristen Tomosa 1 on the implementation of the Kurikulum Merdeka. This research focuses on how students view the curriculum in terms of understanding, learning experiences, emotional responses, and expectations. To comprehensively explore these perspectives, an appropriate research approach is needed. Therefore, a qualitative descriptive method was used using interviews as the main instrument and classroom observation as the second instrument. Data were analyzed using the Miles et al. (2014) model which includes data condensation, data display, and conclusion drawing. This study involved 25 seventh-grade students as respondents. The results showed that most students viewed Kurikulum Merdeka positively. They consider this curriculum to be more practical, fun, and interesting compared to the previous curriculum. Students expressed their appreciation for hands-on activities, project-based learning, and a more flexible learning process. This research also found that students expect more creative and interactive teaching methods to support their interests and learning styles. This research provides insights into how Kurikulum Merdeka is received by students and highlights their expectations for the learning environment. Keywords: students’ perspectives, kurikulum merdeka.